2017
DOI: 10.3389/fnmol.2017.00248
|View full text |Cite
|
Sign up to set email alerts
|

Translational Identification of Transcriptional Signatures of Major Depression and Antidepressant Response

Abstract: Major depressive disorder (MDD) is a highly prevalent mental illness whose therapy management remains uncertain, with more than 20% of patients who do not achieve response to antidepressants. Therefore, identification of reliable biomarkers to predict response to treatment will greatly improve MDD patient medical care. Due to the inaccessibility and lack of brain tissues from living MDD patients to study depression, researches using animal models have been useful in improving sensitivity and specificity of ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
43
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 75 publications
(91 reference statements)
3
43
0
1
Order By: Relevance
“…Transcriptome changes, assessed by differential expression, were relatively small, which is consistent with previous reports despite the different methodologies employed in the various studies (21,22). Also in line with previous reports, most changes were observed in the hippocampus (21,22,56), confirming its sensitivity to stress (57). Our data highlight that despite the tissue-specific differential expression of genes, in particular in the hypothalamus compared to the hippocampus and prefrontal cortex, many enriched biological processes were shared across brain regions.…”
Section: Close Association Between Rems Enhancement and The Corticostsupporting
confidence: 92%
See 3 more Smart Citations
“…Transcriptome changes, assessed by differential expression, were relatively small, which is consistent with previous reports despite the different methodologies employed in the various studies (21,22). Also in line with previous reports, most changes were observed in the hippocampus (21,22,56), confirming its sensitivity to stress (57). Our data highlight that despite the tissue-specific differential expression of genes, in particular in the hypothalamus compared to the hippocampus and prefrontal cortex, many enriched biological processes were shared across brain regions.…”
Section: Close Association Between Rems Enhancement and The Corticostsupporting
confidence: 92%
“…Transcripts and associated processes affected by 9-week exposure to chronic mild stress. Transcriptome changes, assessed by differential expression, were relatively small, which is consistent with previous reports despite the different methodologies employed in the various studies (21,22). Also in line with previous reports, most changes were observed in the hippocampus (21,22,56), confirming its sensitivity to stress (57).…”
Section: Close Association Between Rems Enhancement and The Corticostsupporting
confidence: 91%
See 2 more Smart Citations
“…Since MDD is heterogeneous, it has been suggested that different animal models may help to identify both the diversity of the causes and the shared mechanisms underlying common symptoms of the human disease [11]. This approach has allowed the identification of common transcriptional dysregulations between rodent models and MDD patients [12][13][14].…”
Section: Introductionmentioning
confidence: 99%